In silico Evaluation on the Inhibition Efficacy of Five Antivirals on SARS-CoV-2 Protease (COVID-19) - Raphael, Vinod Palayoor; Shanmughan, Shaju Kanimangalath (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: All over the world rigorous research attempts are going on to find a remedy for the spreading and prevention of the dreadful pandemic of 21st century, the Coronavirus Disease (COVID-19). To discover an effective drug for curing and a preventive vaccine against this disease it will take more than one year. According to some medical practitioners certain antivirals which are used for other diseases can cure COVID-19. Aim: In the present investigation, five antivirals claiming to be effective therapeutic agents to mitigate the symptoms of COVID-19 were screened using computational docking studies on the main protease of coronavirus. Materials and Methods: Five antivirals considered are Favipiravir (FVR), Remdesivir (RMR), Hydroxychloroquine (HCQ), Lopinavir (LVR) and Ritonavir (RVR). The first three agents FVR, RMR and HCQ are used for the treatment of influenza, ebola and malaria respectively. Lopinavir and Ritonavir are the anti-HIV drugs. Favipiravir and Remdesivir are prod rugs and the active nucleotide metabolites (FVR-RTP and RMR-NTP) were taken for in silico docking investigations. AutoDockvina, EduPyMoL and Discovery Studio software’s were used for the computational evaluation. Results: Among the studied molecules HCQ displayed lowest score for the binding energy (-6.1 kcal/mol) and LPR showed the highest value (-8.1 kcal/mol) on SARS-CoV-2 protease. The binding energy of the antivirals on the protease follows the order HCQ <RVR <RMR–NTP <FPR–RTP <LPR. Various interactions of the antivirals with the binding pocket of the protease are well explained using 2D and 3D plots. Conclusion: Poor inhibition was noted for HCQ in the protease binding pocket and hence the therapy using this drug for COVID-19 may not be effective. LPR displayed maximum value of binding capacity on the receptor. FPR-RTP interacted well on the protease with seven H-bonds. RVR and RMR molecules also bound the receptor using strong favourable binding forces.
Keywords: COVID-19; Docking; Inhibitor; Protease; Lopinavir; Ritonavir